Letter to Chairman State Hospital Boards of Trustees; from E.F. Galioni - E.F. Galioni:::::: (1968)
This letter to the unknown use is to invite them to attend a meeting of Chairmen of the State Hospital Boards of Trustees which will be held Tuesday, March 26th at 10:00 am. Some of the topics that will be discussed in this meeting are the following: (1) Reagan's recently announced 14 point mental health program. (2) 1968-69 budget. (3) Plans for mentally retarded. (4) Maintenance of level of care in the hospitals for the mentally ill.